2014
DOI: 10.1371/journal.pgen.1004709
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Endoderm-Derived Taste Sensory Organs Requires a Pax9-Dependent Expansion of Embryonic Taste Bud Progenitor Cells

Abstract: In mammals, taste buds develop in different regions of the oral cavity. Small epithelial protrusions form fungiform papillae on the ectoderm-derived dorsum of the tongue and contain one or few taste buds, while taste buds in the soft palate develop without distinct papilla structures. In contrast, the endoderm-derived circumvallate and foliate papillae located at the back of the tongue contain a large number of taste buds. These taste buds cluster in deep epithelial trenches, which are generated by intercalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 63 publications
(79 reference statements)
1
24
0
Order By: Relevance
“…Whereas anterior tongue FPs have an ectodermal embryonic origin, the posterior tongue tissues and large circumvallate papilla (CV) have endodermal derivation [55,56] and could be affected differently by HH/GLI suppression. In contrast to the single TB in rodent FP, the CV contains a few hundred taste buds in dense physical juxtaposition in walls of the papilla trenches [57].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas anterior tongue FPs have an ectodermal embryonic origin, the posterior tongue tissues and large circumvallate papilla (CV) have endodermal derivation [55,56] and could be affected differently by HH/GLI suppression. In contrast to the single TB in rodent FP, the CV contains a few hundred taste buds in dense physical juxtaposition in walls of the papilla trenches [57].…”
Section: Resultsmentioning
confidence: 99%
“…That loss of SMO in the interplacodal epithelium of K14-CRE/Smo f/f mutant tongues caused no tongue defects ( S2I–S2J’ Fig ) further demonstrates a temporal requirement for SHH signaling in tongue development. K14-CRE activity in the LE is late onset (≈ E13.5) ( S2K–S2N Fig ) [ 42 ], and taste placodes as well as TBs do not express K14 [ 29 ]. Together, these findings point to a restricted period before E12.5 during which loss of SHH signaling induces tongue defects and support previous findings in rat tongue organ cultures [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Pax9 ‐/‐ mutants were recently found to display a hypoplastic CV and trench epithelium defects (Kist et al, ). We have shown that Pax9 is a potential target gene of Tbx1 and its expression is modulated by Ripply3 in the PA (Ivins et al, ; Okubo et al, ).…”
Section: Resultsmentioning
confidence: 99%